Growing old in Christ - Hauerwas, Stanley; Stoneking, Carole Bailey; Meilor, Keith G.; Cloutier, David (Grand Rapids, MI Eerdmans, 2003)
Includes bibliographical references and index.
Keywords: Growing old -- Biblical teaching